Tingginya Frekuensi Minum Teh Mempengaruhi Kejadian Anemia Ibu Hamil - Nabilla Chindi Cantika; Tutik Rahayu; Sri Wahyuni (Journal of Health, Medical, and Psychological Studies, 2025)
Gestational anemia is a health issue that contributes to high Maternal Mortality Rates (MMR) and infant complications, such as Low Birth Weight (LBW). This study aims to determine the correlation between the frequency of tea consumption and the incidence of anemia. This quantitative study employed a cross-sectional approach, with a total of 114 respondents selected via consecutive sampling. The research instruments included demographic data (maternal age, gestational age, weight, height, mid-upper arm circumference/MUAC, and hemoglobin levels) and a Food Frequency Questionnaire (FFQ). Data were analyzed using univariate and bivariate (Chi-square) analysis. The results showed a significant correlation between the frequency of tea consumption in pregnant women and the incidence of anemia (p-value 0.011). Consequently, it is recommended to limit tea intake and avoid consuming it alongside meals or supplements to maintain maternal and fetal hematological stability; this is because the tannin content in tea acts as a chelating agent for iron, thereby inhibiting intestinal absorption and decreasing hemoglobin levels.